Ameloblastic Fibroodontoma of the Mandible with Normal Karyotype in a Pediatric Patient. (9th August 2012) - Manor, Esther; Kan, Elena; Bodner, Lipa
Abstract : Background . Ameloblastic fibroodontoma (AFO) is a rare mixed odontogenic tumor with epithelial and mesenchymal components. AFO presents as a painless swelling in the mandible or maxilla. Radiographs show a well-defined radiolucent area containing various amounts of radiopaque material of irregular size and form. The common treatment is enucleation. It is not an aggressive tumor but recurrence and malignant transformation are possible. Methods . An AFO of the mandible of a 3-year-old female is reported. Panoramic radiograph and CT scan revealed a unilocular lesion with radiopaque center and radiolucent margins. Enucleation was performed with a good outcome. Results . Histopathology was a classic AFO. The karyotype was normal. No recurrence was noted at 12 months. Conclusions . As it is a benign tumor with low recurrence rate, conservative surgery is the treatment of choice. As malignant transformation to ameloblastic fibrosarcoma or ameloblastic odontosarcoma is possible despite the normal karyotype, long-term followup is recommended.